A Cross-Sectional Study on Attitude and Barriers to Interprofessional Collaboration in Hospitals Among Health Care Professionals - Sana Jabbar MS; Hafiza Shabnum Noor MS; Ghazal Awais Butt MS; Syeda Mariyam Zahra MS; Aleena Irum MS; Saadia Manzoor MS; Tahreem Mukhtar MS; Muhammad Rahil Aslam MPhil (SAGE Publishing, 2023)
The need for an effective health personnel team is important due to the increasing complexity of patient care and increasing co-morbidities. Interprofessional collaboration (IPC) among healthcare professionals offers appropriate collaborative management for humans. This study aimed to assess the attitude and barriers to IPC in hospitals among healthcare professionals in Lahore, Pakistan. A cross-sectional study was conducted using a convenience sampling technique. Healthcare professionals (speech-language pathologists, audiologists, physiotherapists, occupational therapists, psychologists, psychiatrists, neurologists, ENT specialists, pediatricians, dentists, and nursing staff) working at Children Hospital, Shaikh Zayed Hospital, Pakistan Society for the Rehabilitation of the Disabled (PSRD), Lahore, Pakistan were included. The paper and online survey questionnaire composed in the google form and attitudes toward healthcare teams scale (ATHCT) and barriers scale toward interprofessional collaboration were used. Statistical package for the social sciences (SPSS) version 21 was used to analyze the survey data through frequency analyses and percentage distributions. Most of the respondents (response rate = 88.1%) had positive attitudes toward IPC and strongly agreed on 9 positive statements in ATHCT. Statistically, Major barriers were role and leadership ambiguity 68.6%, different goals of individual team members 68.1%, and 53.3% strongly agreed on the difference in levels of authority, power, expertise, and income. Although healthcare professionals have an optimistic attitude toward IPC, several healthcare professionals come across challenges during the practice of IPC. To overcome the analyzed barriers, the higher healthcare authorities must encourage interprofessional collaborative strategies and models.